Delivering on the WTO Round : a high-level government-business dialogue 2026-02-16T02:35:12+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... (ESCAP studies in trade and investment ;, 2005)

(untitled)
The articles in this publication provide insights into the status of the negotiations in the main areas of the Doha Development Agenda and interlinkages between trade liberalization in those areas to business and economic development in Asia and the Pacific. It contains both qualitative and quantitative assessments of trade liberalization at multilateral regional/bilateral levels for poverty reduction and development. Special attention is given to harnessing the trade negotiation process to the realization of the Millennium Development Goals.--Publisher's description